Implementation Of The Joyfull Learning Method To Improve Literacy For Children In Tadika Mysarah Padang Serai Kedah, Malaysia - Kurnianda, Indri; Rahimah, Rahimah (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
The Joyfull Learning Method is a revolutionary approach in the world of early childhood education that emphasizes learning through positive experiences, creativity and fun interactions. This research evaluates the effectiveness of the Joyfull Learning method in increasing the literacy of children aged 4-6 years in Tadika Mysarah Padang Serai, Kedah. This research uses a qualitative approach with a case study method, which includes observations over a 1 month period, interviews with teachers and parents, as well as analysis of curriculum materials used in the Joyfull Learning method. The research results show that the Joyfull Learning method is effective in creating a learning environment that stimulates children's interest and creativity. During the observation period, children responded positively, demonstrated high levels of participation in literacy activities, and demonstrated an increase in interest in learning to read and write. The conclusion of this research is that the Joyfull Learning method is a very effective tool in increasing the literacy of children aged 4-6 years in Tadika Mysarah Padang Serai.